4x+3-10=6x-2

Simple and best practice solution for 4x+3-10=6x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+3-10=6x-2 equation:


Simplifying
4x + 3 + -10 = 6x + -2

Reorder the terms:
3 + -10 + 4x = 6x + -2

Combine like terms: 3 + -10 = -7
-7 + 4x = 6x + -2

Reorder the terms:
-7 + 4x = -2 + 6x

Solving
-7 + 4x = -2 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-7 + 4x + -6x = -2 + 6x + -6x

Combine like terms: 4x + -6x = -2x
-7 + -2x = -2 + 6x + -6x

Combine like terms: 6x + -6x = 0
-7 + -2x = -2 + 0
-7 + -2x = -2

Add '7' to each side of the equation.
-7 + 7 + -2x = -2 + 7

Combine like terms: -7 + 7 = 0
0 + -2x = -2 + 7
-2x = -2 + 7

Combine like terms: -2 + 7 = 5
-2x = 5

Divide each side by '-2'.
x = -2.5

Simplifying
x = -2.5

See similar equations:

| (6.78)(0.4-X)= | | (-7c^2-2c-5)+(9c-6)-(16c^2+3)+(-9c^2-7c+7)= | | 110+6x=8x+114 | | y/4= | | 2cos3pi/8*cospi/8 | | 3v-9=33 | | 18*3.14+6*3.14x=420 | | 2cos3pi/8 | | 1.67/0.75 | | F(x)=11x^2+13x | | 2tanx+9=7 | | -5/3X-1/4=-1/6X-1/8 | | 5n^2+8n-10=0 | | 82-62=10x-15x | | (n/4)-5=8 | | 5c-13=8-2c | | -4(0)+2y=7 | | Sec^2x=4tan^2x | | -4x+2(0)=7 | | 4m+3=16 | | 2(-2)+3y=-4 | | 2x+3(0)=-4 | | 3(y-6)-2(5+3y)=5 | | 2(y+6)+1=3y+12-y | | X*4+6=20 | | 8(-1.25)-3y=-10 | | 2x^2-5x=-2is | | 8x-3(0)=-10 | | 3/1*8/9*4/11 | | 2x^2+mx=-2 | | 1/5*3/4*5/7 | | 2(y+6)=3y+12-y |

Equations solver categories